Quantitative Relationship Between Coronary Vasodilator Reserve Assessed by Rubidium-82 PET Imaging and Coronary Artery Stenosis Severity - Anagnostopoulos, Constantinos (2008)
The relationship between myocardial blood flow (MBF) and stenosis severity has been determined previously using cyclotron-produced radiotracers such as (15)O-H(2)O and (13)N-ammonia. An attractive alternative to overcome the limitations related to the use of cyclotron might be to use the generator-produced Rubidium-82 as a flow tracer. The current study was undertaken to investigate the relationship between MBF and coronary vasodilator reserve (CVR) as measured by Rubidium-82 positron emission tomography (PET) and the percent diameter stenosis as defined by quantitative coronary arteriography. METHODS: We prospectively evaluated 22 individuals: 15 patients (60±11 years of age) with angiographically documented coronary artery disease (CAD) and seven age-matched (56±9 years) asymptomatic individuals without risk factors for CAD. Dynamic Rubidium-82 PET was performed at rest and after dipyridamole vasodilation. MBF, CVR and an index of “minimal coronary resistance” (MCR) were assessed in each of the three main coronary territories. RESULTS: Rest and stress MBF in regions subtended by vessels with <50% diameter stenosis was similar to that of the individuals with no risk factors for CAD. As a result, CVR was also similar in the two groups (1.9, interquartile [IQ] range from 1.7 to 2.7 vs. 2.2, IQ range from 2 to 3.4 respectively, p=0.09)). CVR successfully differentiated coronary lesions with stenosis severity 70% to 89% from those with 50% to 69% stenosis (1, IQ range from 1 to 1.3 vs. 1.7, IQ range from 1.4 to 2), respectively, p=0.001. In addition, hyperaemic MBF (r(2)=.74, p<0.001), CVR (r(2)=.69, p<0.001), and MCR (r(2)=.78, p<0.001) measurements were inversely and non-linearly correlated to the percent diameter stenosis on angiography. CONCLUSION: MBF and CVR are inversely and non-linearly correlated to stenosis severity. Quantitative Rubidium-82 PET can be a clinically useful tool for an accurate functional assessment of CAD.